Development of social cost and benefit analysis (SCBA) in the maqaòsid Shariah framework: Narratives on the use of drones for takaful operators - Amirul Afif Muhamat; Ahmad Farouk Zulkifli; Suzana Sulaiman; Geetha Subramaniam; Saadiah Mohamad (Journal of Risk and Financial Management, 2021)
Takaful operators are part of the Islamic financial institutions that are expected to achieve the commercial and social objectives by their stakeholders particularly the takaful participants (policyholders). First, this study aims to postulate a new framework to measure cost effectiveness by including the social and economic benefits of drone-assisted technology in the context of maqaòsid Shariah. Second, the study intends to investigate how the takaful industry can benefit from the drone-assisted technology, particularly in terms of cost reduction. This paper presents an early finding that forms part of a bigger research project which is focusing on the use of drone for disaster victim identification (DVI). This study employs thematic analysis of qualitative research method by engaging key informants who are Shariah expert, drone practitioner and accounting expert. In the context of emerging economies like Malaysia, the adoption of drone is sporadic when some industries such as military and agriculture are quite experienced with it; but for the takaful sector is almost none. This study provides preliminary findings that suggests there is potential of cost effectiveness for drone usage from the perspectives of SCBA in the maqaòsid Shariah framework. The main contributions from this paper are: (1) the new SCBA framework derived from the maqaòsid Shariah perspective and, (2) the application of this framework in examining the cost effectiveness on the use of drones by the takaful operators especially during disaster.
Keywords: 330; maqaòsid; drone; SCBA; Shariah; social cost benefits analysis